Development of diabetic-friendly juices developed from cornslik extract and stability of its antioxidative polyphenolic compounds - Ishak, Wan Rosli (Pusat Pengajian Kesihatan, 2016)
This study aims to develop diabetic-friendly juices developed from cornsilk extract and to investigate stability of it antioxidative polyphenolic compounds. The rats with different dose treatments of cornsilk extract ranging from 400 to 800 mg/kg. Cumulative urine of aqueous extract of cornsilk (AEC) at 400 mg/kg (14.06 ml) and 500 mg/kg (15.21 ml) treatments found to be significantly lower than positive control (21.25 ml). The ED50 of AEC was observed at 454.10 mg/kg. Malaysian AEC had shown a mild diuretic activity in elevating urine and Na+ content at dosages from 500 to 800 mg/kg. Whilst, AEC also showed an effect of potassium sparing diuretics. The highest content of total polyphenol of immature silks was exhibited by ethanol extract (92.21 mg GAE/g) while water extract (64.22 mg GAE/g) had the highest polyphenol content among mature silk extracts. In ABTS assay, all immature silk extracts had higher percentage of inhibition compared to the mature silks. The ethanol extract of immature (EC50 = 0.478 mg/ml) and mature silk (EC50= 0.799 mg/ml) exhibited the strongest antioxidant capacity followed by the water and ethyl acetate extract. Cornsilk extracts are potential ingredient to be applied in food industries and at the same time reducing agriculture wastage._______________________________